Possibility of Harnessing Social Capital to Support the Development of Payment for Environmental Services in Small-Scale Forests: A Case of Jatigede Catchment Area - Nunung Parlinah; Bramasto Nugroho; Muhamad Buce Saleh; Hendrayanto Hendrayanto (Institut Pertanian Bogor (IPB University), 2018)
The concept of social capital has gained attention as a source of support in implementing Payment for Environmental Services (PES). Environmental services, in the context of better water yields in watersheds, is affected by good land cover conditions of forests including small-scale private owned forests. Although some research results indicate that private owned forests are more economic oriented than environmental functions, but its existing social capital can be harnessed to implement PES in small-scale forests. The aim of this study was to analyze the potential of social capital as a source of support in the implementation of PES. The research was conducted by survey method. This research revealeds that the level of trust in local community leaders is very high. This role models can be an key entry point for realizing the PES scheme by strengthening the common knowledge of environmental benefits of small-scale forests and strengthen community norms related to the protection of water resources. Leadership and networking capabilities of the community institution leader give a real influence in collaboration between groups.